Trends in Use and Timing of Intratympanic Corticosteroid Injections for Sudden Sensorineural Hearing Loss. (July 2021) - Jin, Michael C.; Qian, Z. Jason; Cooperman, Shayna P.; Alyono, Jennifer C.
Objective: Oral corticosteroids are treatment mainstays for idiopathic sudden sensorineural hearing loss (SSNHL). Recent studies suggest that intratympanic (IT) steroid injections may be effective as an alternate or adjunctive therapy. We sought to investigate nationwide trends in treatment patterns for SSNHL. Study Design: Retrospective cross-sectional study. Setting: A large nationwide health care claims database spanning 2007 to 2016. Methods: Patients with SSNHL were identified from the IBM Watson Health MarketScan Database. Multivariable logistic, linear, and Cox regression were used for demographic- and comorbidity-adjusted analyses. Results: Overall, 19, 670 patients were included. Between 2007 and 2016, use of oral corticosteroids alone decreased (83.6% to 64.6%, P < .001), while use of IT corticosteroids alone and combination IT-oral corticosteroids increased (IT only, 7.9% to 15.1%, P = .002; IT-oral, 8.5% to 20.4%, P < .001). During the study period, time to treatment initiation decreased for both administration modalities, though more dramatically for IT corticosteroids (IT, 124.0 to 10.6 days, P < .001; oral, 42.6 to 12.7 days, P < .001). In patients receiving both IT and oral corticosteroids, concurrent first-line use increased (25.2% to 52.8%, P < .001). Repeat injections have also become more common but may raise risk of persistent tympanic membrane perforations (vs no injection; hazard ratio [first injection] = 7.95, 95% CI = 5.54-11.42; hazard ratio [fifth or higher injection] = 17.47, 95% CI = 6.93-44.05). Conclusion: SSNHL management increasingly involves early IT steroids as an alternative or adjunctive option to oral steroids. Use of repeat IT corticosteroid injections has also increased but may raise risk of persistent tympanic membrane perforations and subsequent tympanoplasty. Future decision analysis and cost-effectiveness studies are necessary to identify an optimal care pattern for SSNHL.